Low-silver-containing photovoltaic cell main grid paste and preparation method and application thereof
Patent Information
- Application Number
- CN202611082460.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-27
AI Technical Summary
[0007]本发明目的在于提供一种低银含光伏电池主栅浆料,以解决现有低银含浆料存在的印刷性能差、接触电阻高、粉体易氧化、长期可靠性不足的技术问题
(1)有机体系创新带来的印刷性能突破:本发明通过将聚氨酯预聚体与环氧树脂在分子水平上发生化学反应,形成具有单一Tg的均相复合体系(互穿聚合物网络结构),克服了物理共混相容性差的缺陷。该复合体系兼具聚氨酯的柔韧性与环氧树脂的高粘结强度,触变指数达到3.5~8.5,印刷线宽控制在20~40μm,断栅率≤1%,显著优于现有低银含浆料。
Smart Images

Figure CN122991716A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photovoltaic conductive paste technology, specifically relating to a low-silver-containing grid paste suitable for HJT (heterojunction), TOPCon (tunneling oxide passivated contact) and BC (back contact) cells, and particularly to a conductive paste based on a polyurethane-epoxy chemically bonded composite organic system and a spherical silver-coated copper powder with an organic-inorganic composite protective layer on the surface, as well as its preparation method and application. Background Technology
[0002] Photovoltaic cell grid paste is a key material for preparing the surface electrodes of the cell, and its performance directly affects the photoelectric conversion efficiency and manufacturing cost of the cell. With the rapid development of high-efficiency cell technologies such as HJT, TOPCon, and BC, new requirements have been placed on grid paste: on the one hand, the silver content needs to be reduced to control costs, and on the other hand, it needs to meet process requirements such as low-temperature curing, fine-line printing, and low contact resistance.
[0003] To reduce silver content, existing technologies mainly employ silver-coated copper powder as an alternative. However, existing silver-coated copper powders have prominent problems: their morphology is mostly irregular flakes or dendritic, resulting in low powder bulk density (tap density is usually <2.5 g / cm³) and discontinuous conductive network; the copper core is easily oxidized, and the resistance rises sharply in humid and hot environments (85℃ / 85%RH), leading to insufficient long-term reliability; and the binding force with organic carriers is weak, easily causing agglomeration and sedimentation.
[0004] Meanwhile, traditional organic carriers, mainly epoxy resins, ethyl cellulose, and acrylic resins, suffer from drawbacks such as insufficient thixotropy, poor compatibility with low-silver-content systems, and limited performance of single resins. While polyurethane alone offers good flexibility, its bonding strength is insufficient; while epoxy resin alone boasts high bonding strength, it is brittle and exhibits poor low-temperature curing activity. Although existing technologies include blending or modification schemes of polyurethane and epoxy resins (such as CN104312476B, which discloses a polyurethane-modified epoxy resin conductive adhesive), these are typically physical blends or modifications primarily based on epoxy resin, making it difficult to form a truly homogeneous molecular-level composite system. Furthermore, they lack systematic optimization for the printability, contact resistance, and long-term reliability of photovoltaic grid paste under low-silver-content conditions.
[0005] Furthermore, existing literature (such as CN121641535A) proposes using a mixture of silver-coated nickel and silver-coated copper powders to improve oxidation resistance. However, this approach introduces additional metal powders, increasing the complexity of the system, and the use of flake-shaped powders is not conducive to fine-line printing. Another literature (CN121260558A) uses a multilayer coating of silver-coated copper powder with alumina-nickel-silver, but its coating layer is mainly composed of metal / inorganic oxides and does not involve an organic modification layer that forms a chemical bond with the organic resin carrier.
[0006] Therefore, developing a low-silver-containing grid paste that combines low cost, excellent printability, low contact resistance, and high environmental reliability is of great significance for promoting the industrial application of high-efficiency battery technology. Summary of the Invention
[0007] The purpose of this invention is to provide a low-silver photovoltaic cell busbar paste to solve the technical problems of existing low-silver pastes, such as poor printability, high contact resistance, easy oxidation of powder, and insufficient long-term reliability.
[0008] The technical solution adopted by this invention to solve its technical problem is: A low-silver photovoltaic cell busbar paste includes an organic binder, conductive powder, and additives; wherein, The organic adhesive comprises a composite resin system formed by the chemical reaction of a polyurethane prepolymer and an epoxy resin, wherein the DSC curve of the composite resin system shows a single glass transition temperature. The conductive powder comprises near-spherical silver-coated copper powder, the near-spherical silver-coated copper powder having an aspect ratio of 1.0 to 1.5 and a tap density of 2.5 to 5.5 g / cm³, and the surface of the near-spherical silver-coated copper powder having an organic-inorganic composite protective layer, the organic-inorganic composite protective layer being composed of an organic modifier and an inorganic modifier, the formation method being to first modify the surface of the silver-coated copper powder with an organic modifier, and then coat the modified surface with an inorganic modifier; The total mass content of silver in the slurry is 10% to 40%.
[0009] Preferably, the composite resin system is an interpenetrating polymer network structure formed by polyurethane and epoxy resin, and is prepared by a method comprising the following steps: (a) reacting a polyol component with a diisocyanate to obtain a polyurethane prepolymer; (b) reacting the polyurethane prepolymer with an epoxy resin at 50–100°C for 1–4 hours.
[0010] Preferably, the polyol component comprises a mixture of polyester polyol and polyether polyol with a hydroxyl value of 30-150 mg KOH / g, wherein the mass ratio of the two is 1:0.3 to 1:2; the diisocyanate is selected from one or more of diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, hexamethylene diisocyanate trimer, and isophorone diisocyanate.
[0011] Preferably, the epoxy resin is selected from one or more of bisphenol A type epoxy resin, bisphenol F type epoxy resin, and alicyclic epoxy resin, and the epoxy equivalent is 150-500 g / eq.
[0012] Preferably, the spherical silver-coated copper powder has a particle size D50 of 2.5–6.0 μm, an aspect ratio of 1.0–1.3, a tap density of 3.5–5.5 g / cm³, a specific surface area of 0.5–2.0 m² / g, a silver layer thickness of 50–200 nm, and a silver coating rate of ≥99%.
[0013] Preferably, the organic modifier is selected from one or more of silane coupling agents, titanate coupling agents, phosphate esters, stearic acid, oleic acid, and benzotriazole; the inorganic modifier is selected from one or more of silicon dioxide, carbon nanotubes, and graphene.
[0014] Preferably, the additives include one or more of dispersants, leveling agents, thixotropic agents, adhesion promoters, and curing accelerators; the dispersant is a high molecular weight block copolymer containing anchoring groups, wherein the anchoring groups are selected from at least one of phosphate ester groups, carboxylic acid groups, and amine groups; the thixotropic agent is selected from one or more of hydrogenated castor oil, polyamide wax, and fumed silica; and the curing accelerator is selected from one or more of imidazole derivatives, tertiary amine derivatives, and organometallic salts.
[0015] Preferably, based on the total mass of the slurry as 100%, the mass percentage of each component is as follows: organic binder 4% to 6%, solvent 1.5% to 3%, silver powder 0% to 32%, spherical silver-coated copper powder 60% to 88%, and additives 0.5% to 1%.
[0016] Preferably, the thixotropic index of the slurry is 3.5–8.5, the printing linewidth is 20–40 μm, and the broken grid rate is ≤1%; the volume resistivity after curing is ≤10 × 10⁻⁶. -6 The contact resistance with the TCO layer is ≤0.5 mΩ·cm. 2 Welding tensile strength ≥ 1.5 N / mm.
[0017] A second aspect of the present invention provides a method for preparing the low-silver photovoltaic cell busbar paste, comprising the following steps: (1) Preparation of organic adhesive: The polyurethane prepolymer is mixed with epoxy resin and reacted at 50-100°C for 1-4 hours. Solvent and optional additives are added, stirred evenly, and filtered to obtain organic adhesive; the polyurethane prepolymer is prepared by reacting polyol component with diisocyanate at 60-90°C for 2-4 hours. (2) Preparation of conductive powder: Spherical silver-coated copper powder is used. First, its surface is modified with an organic modifier, and then an inorganic modifier is coated on the surface of the modified powder to obtain spherical silver-coated copper powder with an organic-inorganic composite protective layer on the surface; the mass ratio of the organic modifier to the spherical silver-coated copper powder is 0.5:100 to 5:100, and the coating amount of the inorganic modifier is 0.1% to 3% of the mass of the spherical silver-coated copper powder; (3) The conductive powder obtained in step (2) is mixed with the organic binder obtained in step (1) and optional additional silver powder and additives, dispersed evenly, and ground to obtain the low silver content photovoltaic cell grid paste.
[0018] A third aspect of the present invention provides the application of the slurry in the preparation of the main grid electrode of a photovoltaic cell, wherein the photovoltaic cell is an HJT cell, a TOPCon cell, or a BC cell.
[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) Breakthrough in printing performance brought about by the innovation of organic system: This invention overcomes the defect of poor compatibility of physical blending by chemically reacting polyurethane prepolymer and epoxy resin at the molecular level to form a homogeneous composite system (interpenetrating polymer network structure) with a single Tg. The composite system combines the flexibility of polyurethane with the high bonding strength of epoxy resin, with a thixotropic index of 3.5 to 8.5, a printing linewidth controlled at 20 to 40 μm, and a grid breakage rate of ≤1%, which is significantly better than existing low silver content pastes.
[0020] (2) Breakthrough in reliability brought about by innovative protective layer: This invention adopts a composite protective layer structure of "organic modification first, followed by inorganic coating". The organic modifier (such as silane coupling agent) can bond with the oxide or silver layer on the surface of the copper core and react with the active functional groups in the organic carrier to form a chemical bonding interface; the outer inorganic modifier (such as silicon dioxide) provides a dense physical barrier. This composite protective layer makes the resistance change rate ≤10% after 1000h aging at double 85 (85℃ / 85%RH), solving the industry problem of easy oxidation of silver-coated copper powder.
[0021] (3) Breakthrough in electrical properties brought about by near-spherical powder: This invention uses near-spherical silver-coated copper powder with an aspect ratio of 1.0 to 1.5 and a tap density as high as 3.5 to 5.5 g / cm³. 3 It can form a dense conductive network in an organic carrier. The volume resistivity after curing is ≤10×10⁻⁶. -6 The electrical properties are ≤0.5mΩ·cm, with a contact resistance of ≤0.5mΩ·cm² with the TCO layer and a welding pull force ≥1.5N / mm, reaching or even exceeding the level of traditional high silver content pastes.
[0022] (4) Significant low-cost advantage: The total mass content of silver in the paste of this invention is controlled at 10% to 40%, which reduces the amount of silver used by 50% to 80% compared with traditional main grid silver paste (silver content 70% to 90%), and reduces material costs by 50% to 70%, thus significantly reducing the manufacturing cost of photovoltaic cells. At the same time, the curing temperature is 170 to 210°C, which is lower than that of traditional high-temperature sintering pastes, reducing production energy consumption.
[0023] (5) Wide applicability: The slurry of this invention can simultaneously meet the technical requirements of three mainstream high-efficiency batteries: HJT battery (low temperature curing ≤200℃), TOPCon battery (medium temperature curing) and BC battery (high precision printing), and has wide applicability. Attached Figure Description
[0024] Figure 1 Infrared (IR) spectrum of the composite resin system synthesized in Example 1 of this invention.
[0025] Figure 2 Infrared (IR) spectra of the interactions of the organic systems used in Example 1 of this invention.
[0026] Figure 3 The scanning electron microscope (SEM) image of the spherical silver-coated copper powder used in Example 2 of this invention.
[0027] Figure 4 Example 3 of the present invention: Scanning electron microscope (SEM) image of the cross-section of the grid lines after the paste is printed. Detailed Implementation
[0028] For ease of understanding, based on the technical solutions of the present invention, those skilled in the art can propose various interchangeable structural methods and implementations without altering the essential spirit of the invention. Therefore, the following detailed embodiments and accompanying drawings are merely illustrative examples of the technical solutions of the present invention and should not be considered as the entirety of the invention or as limitations or restrictions on the technical solutions of the present invention. Example 1
[0029] 1. Raw material preparation.
[0030] (1) Raw materials for the synthesis of organic adhesives: Polyester polyol (hydroxyl value 56mgKOH / g): 50g; Polyether polyol (hydroxyl value 56mgKOH / g): 50g; Diphenylmethane diisocyanate (MDI): 60g; Bisphenol A type epoxy resin (epoxy equivalent 190): 30g; 1,4-Butanediol: 5g; Dibutyltin dilaurate: 0.1g.
[0031] (2) Conductive powder: Spherical silver-coated copper powder: D50=3.8μm, aspect ratio 1.1, tap density 4.9g / cm³, silver layer thickness 80nm, silver coating rate 99.5%. Surface treatment: First, wet modification is performed using KH560 silane coupling agent (organic modifier), with a modification amount of 1.5% of the powder mass; then, silica (inorganic modifier) is coated onto the surface of the modified powder using the sol-gel method, with a coating amount of 0.8% of the powder mass.
[0032] (3) Others: Solvent: Diethylene glycol butyl ether acetate; Thixotropic agent: polyamide wax; Dispersant: Block copolymer containing phosphate ester groups; Curing accelerator: 2-methylimidazole; 2. Preparation of organic adhesives.
[0033] Polyester polyol and polyether polyol were added to a reactor and heated to 110°C for vacuum dehydration for 1.5 hours. The mixture was then cooled to 65°C, and MDI and a catalyst were added. The reaction was carried out under nitrogen protection for 3 hours to obtain a polyurethane prepolymer (isocyanate group content determined to be 4.2%). Epoxy resin was added, and the mixture was heated to 90°C and reacted for 2 hours to allow chemical bonding between the polyurethane prepolymer and the epoxy resin. 1,4-Butanediol was added for chain extension, and the reaction was continued for 1.5 hours. The mixture was then cooled and discharged to obtain a composite resin system. The composite resin exhibited a GPC Mw of 45,000, a DSC Tg of 30°C, an acid value of 12 mg KOH / g, a hydroxyl value of 55 mg KOH / g, and an epoxy value of 0.12 eq / 100g.
[0034] Take 75 parts by weight of the above composite resin, add 25 parts by weight of diethylene glycol butyl ether acetate, stir and dissolve at 80°C, add polyamide wax (thixotropic agent) and 2-methylimidazole (curing accelerator), stir for 45 min, filter through 200 mesh, add dispersant, disperse at 1000 rpm for 20 min in a high-speed disperser to obtain organic adhesive.
[0035] 3. Slurry preparation.
[0036] Based on 100% of the total mass of the slurry: Spherical silver-coated copper powder (silver content 12%): 70%; Organic adhesives: 7%; Solvent (added): 3%; Additives (dispersant 0.5%, polyamide wax 1.5%, others 1%): 3%; The remainder is spherical silver powder (added to 100%, total silver content 12%). The above components were mixed, homogenized, and ground to a fineness of ≤7μm using a three-roll mill to obtain a slurry. Performance test results are shown in Table 1. Example 2
[0037] The difference from Example 1 is as follows: Conductive powder: 82% spherical silver-coated copper powder (silver content 12%) + 18% spherical silver powder (silver content 100%), total conductive powder 91%.
[0038] In the synthesis of composite resin, the ratio of polyester polyol to polyether polyol is adjusted to 1:1.
[0039] Total silver content in the slurry: 25%.
[0040] The performance test results are shown in Table 1. Example 3
[0041] The difference from Example 1 is as follows: Surface modifier for conductive powder: only organic modifier (KH560 silane coupling agent, 8nm thickness), no silica inorganic layer.
[0042] The amount of epoxy resin used in the synthesis of composite resin was adjusted to 20g.
[0043] Suitable for TOPCon batteries, curing temperature 200℃.
[0044] Total silver content in the slurry: 35%.
[0045] The performance test results are shown in Table 1. Example 4
[0046] The difference from Example 1 is as follows: In the synthesis of composite resin, the ratio of polyester polyol to polyether polyol is adjusted to 1:0.5 (increasing the polyester ratio improves rigidity).
[0047] The amount of epoxy resin was adjusted to 50g (to increase the epoxy content and improve the bonding strength).
[0048] The performance test results are shown in Table 1.
[0049] Comparative Example 1 (without protective layer): The difference from Example 1 is that the spherical silver-coated copper powder has no protective layer on its surface (i.e., it has not undergone organic modification and inorganic coating). Other components and preparation methods are the same as in Example 1.
[0050] Comparative Example 2 (Single Polyurethane Carrier): The difference from Example 1 is that the organic adhesive uses only polyurethane resin (the product of chain extension of the polyurethane prepolymer synthesized in Example 1), does not contain epoxy resin, and does not undergo polyurethane-epoxy chemical bonding reaction.
[0051] Comparative Example 3 (Conventional Irregular Silver-Plated Copper Powder): The difference from Example 1 is that flake-shaped silver-coated copper powder (aspect ratio 3.5, tap density 4.2 g / cm³) is used, and there is no protective layer on the surface.
[0052] Comparative Example 4 (commercially available high silver content paste): The difference from Example 1 is that commercially available grid silver paste with a silver content of 91% is used, and there is no silver-coated copper powder.
[0053] Performance testing methods: Viscosity: Brookfield DV2T, 5 rpm, 25°C.
[0054] Thixotropic index: the ratio of viscosity at 6 rpm to viscosity at 60 rpm.
[0055] Fineness: Scraper fineness gauge.
[0056] Volume resistivity: Four-probe method, film thickness measured after curing.
[0057] Contact resistance: TLM method, tested on the TCO layer of HJT cells or the SiNx layer of TOPCon cells.
[0058] Welding tensile strength: 90° peel test after welding.
[0059] Dual 85 reliability: 85℃ / 85%RH, 1000h, test resistance change rate.
[0060] DSC test: N2 atmosphere, heating rate 10℃ / min.
[0061] Test results:
[0062] Results analysis: As can be seen from Examples 1-4, the paste of the present invention achieves excellent thixotropy (thixotropic index ≥ 5.5), low linewidth (≤ 35 μm), low grid breakage rate (≤ 0.8%), and low volume resistivity (≤ 9.5 × 10⁻⁶) under low silver content conditions of 12%-35%. -6 It exhibits high resistance (≤0.28 mΩ·cm²), low contact resistance (≥1.7 N / mm), high weld tensile strength, and good anti-aging properties (double 85 resistance change rate ≤8.2%). DSC tests all showed a single Tg, demonstrating that polyurethane and epoxy resin form a homogeneous chemically bonded system.
[0063] Compared with Example 1, Comparative Example 1 (without protective layer) showed a double 85 resistance change rate of up to 18% and a decrease in welding pull force, demonstrating that the protective layer is crucial for anti-oxidation and interfacial bonding.
[0064] Comparative Example 2 (single polyurethane carrier) has a thixotropic index of only 3.2, a printed linewidth of 48μm, a grid breakage rate of 7.5%, and a volume resistivity that is an order of magnitude higher, demonstrating the necessity of the polyurethane-epoxy composite system.
[0065] Comparative Example 3 (irregular flake powder) showed severe line expansion (62μm) during printing, with both volume resistivity and contact resistance significantly increased, demonstrating the importance of near-spherical powder for low-silver paste.
[0066] While Comparative Example 4 (high silver paste) exhibits excellent performance, its 91% silver content results in high costs. Example 1 of this application, with a silver content of only 12%, achieves a contact resistance (0.18 mΩ·cm²) comparable to Comparative Example 4, similar welding pull strength, and a slightly higher volume resistivity, still within an acceptable range, while reducing costs by approximately 70%, demonstrating significant economic benefits.
[0067] Application Example 1: The paste from Example 1 was screen-printed (400-mesh screen) onto HJT solar cells to form the main grid pattern, and cured at 200°C for 25 minutes. Test results: The main grid linewidth was 28 μm, the aspect ratio was 0.54, and there were no grid breaks; the cell photoelectric conversion efficiency was 24.71% (comparable to 24.70% for the high-silver paste control group); the module EL test showed no dark spots, black spots, or bright / dark lines; the module power decay (1000h) was 1.8%.
[0068] Application Example 2: The paste from Example 3 was printed onto TOPCon solar cells and cured at 200–280°C for 1 minute. Test results: The photoelectric conversion efficiency of the cell was 26.2%, which is basically the same as that of the pure silver busbar on the production line.
[0069] Application Example 3: The paste from Example 2 was printed onto BC solar cells and cured at 200°C for 20 minutes. Test results: Excellent fine-line printability, with a line width of 35 μm; the cell efficiency was basically on par with competing pure silver products.
[0070] The technical scope of this invention is not limited to the content described above. Those skilled in the art can make various modifications and variations to the above embodiments without departing from the technical concept of this invention, and all such modifications and variations should fall within the protection scope of this invention.
Claims
1. A low-silver photovoltaic cell busbar paste, characterized in that, Includes organic binders, conductive powders, and additives; among which, The organic adhesive comprises a composite resin system formed by the chemical reaction of a polyurethane prepolymer and an epoxy resin, wherein the DSC curve of the composite resin system shows a single glass transition temperature. The conductive powder comprises near-spherical silver-coated copper powder, the near-spherical silver-coated copper powder having an aspect ratio of 1.0 to 1.5 and a tap density of 2.5 to 5.5 g / cm³, and the surface of the near-spherical silver-coated copper powder having an organic-inorganic composite protective layer, the organic-inorganic composite protective layer being composed of an organic modifier and an inorganic modifier, the formation method being to first modify the surface of the silver-coated copper powder with an organic modifier, and then coat the modified surface with an inorganic modifier; The total mass content of silver in the slurry is 10% to 40%.
2. The low-silver photovoltaic cell busbar paste according to claim 1, characterized in that, The composite resin system is an interpenetrating polymer network structure formed by polyurethane and epoxy resin, which is prepared by a method including the following steps: (a) The polyol component is reacted with diisocyanate to obtain a polyurethane prepolymer; (b) The polyurethane prepolymer is reacted with epoxy resin at 50-100°C for 1-4 hours to connect the polyurethane segments and epoxy resin segments through chemical bonds. The polyol component comprises a mixture of polyester polyol and polyether polyol with a hydroxyl value of 30-150 mgKOH / g, wherein the mass ratio of the two is 1:0.3-1:2; the diisocyanate is selected from one or more of diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, hexamethylene diisocyanate trimer, and isophorone diisocyanate.
3. The low-silver photovoltaic cell busbar paste according to claim 2, characterized in that, The epoxy resin is selected from one or more of bisphenol A type epoxy resin, bisphenol F type epoxy resin, and alicyclic epoxy resin, and the epoxy equivalent is 150-500 g / eq.
4. The low-silver photovoltaic cell busbar paste according to claim 1, characterized in that, The spherical silver-coated copper powder has a particle size D50 of 2.5–6.0 μm, an aspect ratio of 1.0–1.3, a tap density of 3.5–5.5 g / cm³, a specific surface area of 0.5–2.0 m² / g, a silver layer thickness of 50–200 nm, and a silver coating rate of ≥99%.
5. The low-silver photovoltaic cell grid paste according to claim 1, characterized in that, The organic modifier is selected from one or more of silane coupling agents, titanate coupling agents, phosphate esters, stearic acid, oleic acid, and benzotriazole; the inorganic modifier is selected from one or more of silicon dioxide, carbon nanotubes, and graphene.
6. The low-silver photovoltaic cell busbar paste according to claim 1, characterized in that, The additives include one or more of dispersants, leveling agents, thixotropic agents, adhesion promoters, and curing accelerators; the dispersant is a high molecular weight block copolymer containing anchoring groups, wherein the anchoring groups are selected from at least one of phosphate ester groups, carboxylic acid groups, and amine groups; the thixotropic agent is selected from one or more of hydrogenated castor oil, polyamide wax, and fumed silica; and the curing accelerator is selected from one or more of imidazole derivatives, tertiary amine derivatives, and organometallic salts.
7. The low-silver photovoltaic cell busbar paste according to claim 1, characterized in that, Based on the total mass of the slurry being 100%, the mass percentage of each component is as follows: Organic adhesives 4%–6% Solvent 1.5%–3% Silver powder 0%–32% Spherical silver-coated copper powder: 60%–88% Additives: 0.5%–1%.
8. The low-silver photovoltaic cell busbar paste according to claim 1, characterized in that, The thixotropic index of the slurry is 3.5–8.5, the printing linewidth is 20–40 μm, and the broken grid rate is ≤1%; the volume resistivity after curing is ≤10 × 10⁻⁶. -6 The contact resistance with the TCO layer is ≤0.5 mΩ·cm. 2 Welding tensile strength ≥ 1.5 N / mm.
9. A method for preparing the low-silver photovoltaic cell grid paste according to any one of claims 1-8, characterized in that, Includes the following steps: (1) Preparation of organic adhesive: The polyurethane prepolymer is mixed with epoxy resin and reacted at 50-100°C for 1-4 hours. Solvent and optional additives are added, stirred evenly, and filtered to obtain organic adhesive; the polyurethane prepolymer is prepared by reacting polyol component with diisocyanate at 60-90°C for 2-4 hours. (2) Preparation of conductive powder: Spherical silver-coated copper powder is used. First, its surface is modified with an organic modifier, and then an inorganic modifier is coated on the surface of the modified powder to obtain spherical silver-coated copper powder with an organic-inorganic composite protective layer on the surface; the mass ratio of the organic modifier to the spherical silver-coated copper powder is 0.5:100 to 5:100, and the coating amount of the inorganic modifier is 0.1% to 3% of the mass of the spherical silver-coated copper powder; (3) The conductive powder obtained in step (2) is mixed with the organic binder obtained in step (1) and optional additional silver powder and additives, dispersed evenly, and ground to obtain the low silver content photovoltaic cell grid paste.
10. The application of the low-silver photovoltaic grid paste according to any one of claims 1-8 in the preparation of photovoltaic grid electrodes, characterized in that, The photovoltaic cells are HJT cells, TOPCon cells, or BC cells.
Citation Information
Patent Citations
A silver-coated copper powder conductive adhesive and its preparation method
CN104312476B
Preparation method of silver-coated copper slurry suitable for TOPCON
CN121260558A
Silver-coated nickel and silver-coated copper mixed slurry and preparation method thereof
CN121641535A
